INTEGRATING SCIENCE PROCESS SKILLS IN COOPERATIVE SETTINGS USING MODULES TO IMPROVE COGNITIVE LEARNING OUTCOMES ON THE SOLID ELASTICITY TOPIC - Siombone, Salman Hamja (UIN Sunan Gunung Djati Bandung, 2025)
This study aims to combine science process skills and students' cognitive abilities and improve students' cognitive learning outcomes by implementing the physics learning module in a cooperative setting. This research was conducted at SMA Negeri 3 Ambon, and this type is quantitative descriptive research. The design used in this study is the One-Group Pretest-Posttest Design. The sample in this study was class X MIA3, totaling 33 people, and it was taken using a purposive sampling technique. The instruments used in this study were test instruments, Student Activity Sheets, and non-test instrument rubrics. The research data shows that students' average initial cognitive ability is very low, achieving 28.78. In contrast, the final cognitive ability of students increases with achievement of 83.39. Student's cognitive ability through student worksheets has an average achievement of 85.51, while the average percentage of concept mastery with student worksheets is above 80%. Science process skills (SPS) with the highest average achievement are in conducting observations, namely 91.67, while the skill with the lowest is in planning experiments, namely 80.52. The difficulty level and complexity of the skills developed influence the high and low average SPS achievements. The results of the research data calculation obtained an increase in the achievement of learning outcomes of the N-gain value of 0.78, which indicates an increase in learning outcomes with a high category. The results of this study suggest that integrating SPS through learning modules in a cooperative setting can improve the physics learning outcomes on the solids elasticity concept.